A influência da orientação para o mercado internacional no desenvolvimento da inovação e ecoinovação - Dourado, Fábio Alves (2018)
Market orientation has been proven to be an important strategy for the competitiveness to organizations. Close relationship to customers, understanding of competitors and integration of the various departments are factors that influence the appearance of innovative ideas. In this context, seek to understand the influence of market orientation in the international environment and how the market influences the development of innovation. In addition, if the great concern of the 21st century is sustainable development and the adoption of practices that minimize environmental impact, the study proposed not only to understand conventional innovation but also to understand eco-innovation in the international context. This dissertation innovates by relating guidance to the International Market with innovation and eco-innovation. They were analyzed by a structural equations model. The results indicate that there is a positive association between Guidance for the International Market, innovation and eco-innovation. This dissertation contributes to understanding the influence of the market when the company internationalized comparing the processes of innovation and eco-innovations. Although the eco-innovations being more complex with high costs of implantation the companies when inserted in the international environment develop the eco-innovation. The result from the managerial point of view, shows that organizations need to consider sustainability in the internationalization process.